Antibacterial and antiviral sprayed ultra-high performance decorative concrete and method for preparing the same
Patent Information
- Application Number
- CN202610536698.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-22
- Publication Date
- 2026-10-02
AI Technical Summary
[0003]尽管传统浇筑工法在大型平面板的生产中具有一定优势,但在生产大型3D曲面造型的UHPC装饰板时,该工法的局限性十分明显:一方面,针对复杂的3D曲面结构,模具制造的难度极大,需要定制化设计和加工,导致模具制作成本大幅增加;另一方面,浇筑过程中材料的流动和成型质量难以精准管控,容易出现成型缺陷,影响装饰板的整体性能和美观度,无法满足复杂3D曲面UHPC装饰板的生产需求,因此,针对以上现状,迫切需要开发一种抗菌抗病毒喷射型超高性能装饰混凝土及其制备方法,以克服当前实际应用中的不足
本发明的抗菌抗病毒喷射型超高性能装饰混凝土采用喷射工法进行生产制造,可直接用于复杂3D曲面UHPC装饰板的制造,有效降低了模具制作的难度和费用,同时便于管控成型质量,解决了传统浇筑工法在复杂造型装饰板生产中的痛点;
Smart Images

Figure CN122853774A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of exterior wall decorative panel manufacturing, specifically to an antibacterial and antiviral sprayed ultra-high performance decorative concrete and its preparation method. Background Technology
[0002] UHPC (Ultra-High-Pressure Polymer) exterior wall panels are a common type of exterior wall decoration material. Compared to GRC (Glass Reinforced Concrete) panels, they have higher bending and compressive strength, making them suitable for manufacturing extra-large and curved panels, and widely used in the architectural decoration field. Traditionally, UHPC panels are manufactured using a casting method, which is simple, fast, and produces panels with smooth surfaces and backs, resulting in good aesthetics, especially suitable for the production of large flat panels. Currently, antibacterial and antiviral properties have become an indispensable functional requirement for various decorative materials, and the market demand for decorative materials with antibacterial and antiviral properties is increasingly urgent.
[0003] While traditional casting methods have certain advantages in the production of large flat slabs, their limitations are quite evident when producing large 3D curved UHPC decorative panels. On the one hand, the mold manufacturing process is extremely difficult for complex 3D curved structures, requiring customized design and processing, which significantly increases mold production costs. On the other hand, the flow of materials and the quality of molding are difficult to control precisely during the casting process, easily leading to molding defects that affect the overall performance and aesthetics of the decorative panels, failing to meet the production requirements of complex 3D curved UHPC decorative panels. Therefore, in response to the above situation, there is an urgent need to develop an antibacterial and antiviral sprayed ultra-high performance decorative concrete and its preparation method to overcome the shortcomings in current practical applications. Summary of the Invention
[0004] The purpose of this invention is to provide an antibacterial and antiviral sprayed ultra-high performance decorative concrete and its preparation method, so as to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: An antibacterial and antiviral sprayed ultra-high performance decorative concrete includes dry powder, liquid polycarboxylate superplasticizer, and alkali-resistant continuous glass fiber coarse sand; The dry powder, by weight, comprises 40-45 parts white silicate cement, 5-10 parts silica fume, 2-5 parts metakaolin, 1-2 parts expansion agent, 40-50 parts natural colored sand, 1-1.5 parts redispersible latex powder, and 0.5-1.0 parts inorganic zinc oxide antibacterial agent. The amount of the liquid polycarboxylate superplasticizer used is 0.9-1.0% of the total mass of the dry powder. The amount of alkali-resistant continuous glass fiber coarse sand used is 5.8% of the wet mixture mass; The wet mix is made by mixing dry powder with mixing water, and the amount of mixing water is 11-13% of the mass of the dry powder; the compressive strength of the decorative concrete is >120MPa and the flexural strength is >12MPa.
[0006] As a further aspect of the present invention: the white silicate cement is PW52.5 grade, with a whiteness ≥85% and a specific surface area of... .
[0007] As a further aspect of the present invention: the silica fume is white zirconium-containing microsilica powder with a specific surface area of... Zirconium oxide content ≥10%.
[0008] As a further aspect of the present invention, the average particle size of the inorganic zinc oxide antibacterial agent is ≤2μm.
[0009] As a further aspect of the present invention: the liquid polycarboxylate superplasticizer has a solid content of 50±1%, a pH value of 6.5±1, and a viscosity of <2000mPa·s.
[0010] As a further aspect of the present invention: the tensile strength of the monofilament of the alkali-resistant continuous glass fiber coarse sand elastic modulus The diameter of a single filament is ≤14μm.
[0011] A method for preparing antibacterial and antiviral sprayed ultra-high performance decorative concrete includes the following steps: (1) Mixing: According to the above proportions, after the dry powder components are mixed evenly, add the pre-mixed liquid polycarboxylate superplasticizer and mixing water, and wet mix to make a uniform wet mix. (2) Preparation before spraying: Use a small CNC GRC spraying machine to adjust the fiber spraying speed so that the amount of alkali-resistant continuous glass fiber coarse sand meets the requirements of claim 1; (3) Surface spraying: Spraying wet mix containing alkali-resistant continuous glass fiber coarse sand into the mold to form a surface layer with a thickness of 1-5mm; (4) Structural layer spraying and compaction: Spray a wet mixture containing alkali-resistant continuous glass fiber coarse sand onto the surface layer to the specified thickness, and compact it by rolling it back and forth with a manual roller; (5) Surface smoothing: After removing excess material, smooth the surface to obtain antibacterial and antiviral sprayed ultra-high performance decorative concrete.
[0012] As a further aspect of the present invention: in step (1), the dry mixing time is 5 min and the wet mixing time is 10 min.
[0013] As a further aspect of the present invention: in step (2), before spraying, wet mixed material and alkali-resistant continuous glass fiber coarse sand are sprayed for 30 seconds each and weighed, and the fiber spraying speed is adjusted according to the weighing results.
[0014] As a further embodiment of the present invention: the liquid polycarboxylate superplasticizer is pre-mixed evenly with stirring water and then added to the dry powder for wet mixing.
[0015] Compared with the prior art, the beneficial effects of the present invention are: The antibacterial and antiviral sprayed ultra-high performance decorative concrete of this invention is produced by spraying method and can be directly used in the manufacture of complex 3D curved UHPC decorative panels. It effectively reduces the difficulty and cost of mold making, and at the same time facilitates the control of molding quality, solving the pain points of traditional casting method in the production of complex shaped decorative panels. This decorative concrete has excellent mechanical properties, with a compressive strength greater than 120MPa and a flexural strength greater than 12MPa, fully meeting the relevant standards of decorative UHPC. It can provide reliable structural support for ultra-large decorative panels and curved panels, ensuring the long-term performance of the products. The material contains antibacterial agents, which gives the UHPC decorative panel excellent antibacterial and antiviral properties. It can effectively inhibit the growth and spread of related bacteria and viruses, and is beneficial to human health when in contact with people, thus meeting the core requirement of current decorative materials for antibacterial and antiviral functions. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the structure of antibacterial and antiviral sprayed ultra-high performance decorative concrete in an embodiment of the present invention; The red part is the product surface layer, 1-5mm thick, fiber-free, with a smooth surface, serving a decorative purpose; the blue part is the structural layer, containing fibers, which provides overall load-bearing function, and is compacted with a roller after spraying; the orange part is scraped off with a scraper and trowel to control the thickness and smooth the surface. Detailed Implementation
[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.
[0019] Please see Figure 1This invention provides an antibacterial and antiviral sprayed ultra-high performance decorative concrete and its preparation method, which can solve the problems of high mold cost and difficulty in quality control when producing large 3D curved UHPC decorative panels using traditional casting methods. It also meets the functional requirements of antibacterial and antiviral decorative materials. The specific details are as follows: I. Composition and Specifications of Raw Materials 1. Dry powder (by weight): White silicate cement: 40-45 parts, using PW52.5 grade cement, whiteness ≥85%, specific surface area This cement possesses high-strength cementitious properties, providing core mechanical support for concrete and forming the basis for achieving compressive strength >120MPa and flexural strength >12MPa. Simultaneously, its white color ensures the clean appearance of the decorative panels.
[0020] Silica fume: 5-10 parts, using white zirconium-containing microsilica powder, specific surface area Zirconium oxide ( The silica fume content is 10%. The high specific surface area of silica fume can fill the hydration pores of cement, significantly improving the density of the material, which enhances mechanical strength and durability without affecting the decorative texture of the decorative panel.
[0021] Metakaolin: 2-5 parts, pale yellow powder, particle size 1250 mesh. , As an active admixture, it can undergo secondary reactions with cement hydration products, optimizing the microstructure and reducing material shrinkage (shrinkage rate as low as [value missing] after 28 days of curing). This helps prevent the decorative panels from cracking and improves volume stability.
[0022] Expanding agent: 1-2 parts, calcium oxide and calcium sulfoaluminate complex, specific surface area By compensating for concrete shrinkage through hydration expansion, crack formation is further suppressed, ensuring the integrity of the decorative panels for long-term use.
[0023] Natural colored sand: 40-50 parts, made from 200-mesh quartz powder. Quartz powder has excellent wear resistance and decorative properties. Its fine particle size makes the concrete surface smooth and delicate, meeting the aesthetic requirements of exterior wall decoration, while also improving the wear resistance of the material.
[0024] Redispersible latex powder: 1-1.5 parts, white free-flowing powder, apparent density (450±50). The polymer film formed after hydration can improve the material's bonding strength and flexibility, enhance its flowability during application, ensure uniform material adhesion during spraying, and prevent segregation.
[0025] Defoamer: 0-0.01 parts. It can eliminate air bubbles generated during stirring, prevent the formation of pores inside the material, ensure density, and thus improve mechanical properties and surface smoothness.
[0026] Calcium acetate: 0.05-0.15 parts, white powder, chemically pure grade, dosage 0.1%-0.3%. As an early strength agent, it can accelerate cement hydration, improve early strength, stabilize material workability, and ensure the quality of spray molding.
[0027] Antibacterial agent: 0.5-1.0 parts, inorganic zinc oxide antibacterial agent, average particle size ≤2μm. The fine particle size allows it to be uniformly dispersed in concrete, giving the material highly efficient antibacterial and antiviral properties. It can effectively inhibit Escherichia coli, Staphylococcus aureus, and H1N1 influenza A virus, protecting human health.
[0028] 2. Liquid polycarboxylate superplasticizer: The dosage is 0.9-1.0% of the total dry powder mass. It is a brownish-yellow liquid with a solid content of 50±1%, a pH value of 6.5±1, and a viscosity of <2000 mPa·s. Its highly efficient water-reducing effect ensures good material flowability (initial flowability can reach 290-320 mm) even with water added at only 11-13% of the dry powder mass, avoiding a decrease in strength due to an excessively high water-cement ratio.
[0029] 3. Alkali-resistant continuous glass fiber coarse sand: dosage is 5.8% of the wet mixture mass, specification is the tensile strength of a single filament. Elastic modulus It has a specific gravity of 2.68 and a single filament diameter of 14μm. Its excellent tensile strength and alkali resistance can significantly improve the flexural strength (up to 18.2MPa) and toughness of concrete, and it is stable in alkaline environments for a long time, ensuring the long-term mechanical properties of the material.
[0030] II. Preparation Method This invention must be produced using a spraying process, and the specific steps are as follows: 1. Mixing Process: According to the above proportions, pour the dry powder components, including white silicate cement, silica fume, metakaolin, expanding agent, natural colored sand, redispersible latex powder, defoamer, calcium acetate, and antibacterial agent, into a forced mixer (a conventional equipment in this field, such as the JS500 model). Dry mix for 5 minutes to ensure uniform mixing of all components and avoid performance fluctuations due to uneven mixing. After dry mixing, pre-mix the liquid polycarboxylate superplasticizer with mixing water (11-13% of the dry powder mass), pour it into the mixer, and wet mix for 10 minutes to allow the superplasticizer to fully exert its effect and form a uniform, viscous, and fluid wet mix, laying the foundation for subsequent spraying construction. After mixing, pour the wet mix into the hopper of the spraying machine for later use.
[0031] 2. Preparation before spraying: A small CNC GRC spraying machine is used as the spraying equipment. This equipment can precisely control the spraying volume and speed, adapting to the needs of complex 3D curved surface molding. Compared with the traditional casting method, it significantly reduces the difficulty and cost of mold making. Before spraying, the equipment is started to spray the wet mixture for 30 seconds and weigh it, then the fiber is sprayed for 30 seconds and weighed again. The fiber spraying speed is adjusted according to the weighing results to ensure that the fiber weight accounts for 4.0-6.0% of the wet mixture weight. Finally, the alkali-resistant continuous glass fiber coarse sand content is controlled at 5.8% of the wet mixture mass to ensure uniform fiber dispersion and fully exert the reinforcing and toughening effect.
[0032] 3. Surface Coating Spraying: First, spray a fiber-free wet-mix material into the mold as the surface coating, controlling the thickness to 1-5mm. The fiber-free surface coating ensures a smooth and delicate surface, enhancing the decorative effect. At the same time, its dense structure enhances the surface coating's antibacterial and antiviral properties, ensuring health and safety when in contact with people.
[0033] 4. Structural Layer Spraying: After the surface layer is formed, a wet-mixed material containing fibers is sprayed onto it to the specified thickness. The alkali-resistant glass fiber in the structural layer can significantly improve the mechanical strength and structural stability of the decorative panel, meeting the load-bearing requirements of large 3D curved decorative panels. After spraying, it is compacted by rolling back and forth with a hand roller to ensure that the structural layer and the surface layer are tightly bonded, eliminating gaps and air bubbles, and improving overall density.
[0034] 5. Smoothing the surface after spraying: After compaction, use a large scraper to remove excess material, and then use a trowel to smooth the surface to ensure that the overall thickness meets the design requirements and the surface is flat. At the same time, a flat surface is conducive to the uniform performance of antibacterial and antiviral properties and prevents bacteria and viruses from growing in uneven areas.
[0035] The technical solution of the present invention is described in detail below through six specific embodiments. The only difference between the embodiments is the parameters of the raw materials. The preparation process follows the overall technical solution described above. The performance testing standards are as follows: The bulk density after fiber addition is based on JG / J70-2009 "Standard for Test Methods of Basic Properties of Building Mortar"; the 28-day compressive strength and flexural strength are based on GB17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)"; the antibacterial rate is based on ISO22196-2011 "Determination of antibacterial properties of plastics and other non-porous surfaces"; the antiviral activity rate is based on ISO21702:2019 "Determination of antiviral activity of plastics and other non-porous surfaces"; the shrinkage rate is tested after curing at 20℃ and 60% humidity for 28 days. Example 1:
[0036] Raw material proportions (parts by weight): 40.08 parts PW52.5 cement, 7.77 parts silica fume, 2.61 parts metakaolin, 1.57 parts expanding agent, 46.43 parts quartz powder, 1.48 parts adhesive powder, 0.15 parts calcium acetate, 0.05 parts antibacterial agent, total powder weight 100.04 parts; 0.92 parts liquid polycarboxylate superplasticizer (0.92% of total dry powder weight); 12.1 parts mixing water (12.09% of dry powder weight); total wet mix weight 113.08 parts; 6.56 parts alkali-resistant continuous glass fiber coarse sand (5.8% of wet mix weight).
[0037] Performance and effects: The density of the prepared decorative concrete after fiber addition The initial flowability was 290 mm. After adding fibers and vibrating for 25 cycles on a jump table, the flowability was 180 mm. The 28-day shrinkage rate was... The compressive strength after 28 days is 125 MPa, and the flexural strength after 28 days is 17.5 MPa, fully meeting the decorative UHPC standard. The 24-hour antibacterial rate against Escherichia coli and Staphylococcus aureus is 75%, and the antiviral activity rate against H1N1 influenza A virus is 72.5%. Because the amount of antibacterial agent is lower than the 0.5-1.0 part range specified in this invention, the antibacterial and antiviral effects are slightly weaker, but the mechanical properties and construction compatibility are good, and it can be used in decorative scenarios with lower antibacterial requirements. Example 2:
[0038] Raw material proportions (parts by weight): 40.08 parts PW52.5 cement, 7.77 parts silica fume, 2.61 parts metakaolin, 1.57 parts expanding agent, 46.43 parts quartz powder, 1.48 parts adhesive powder, 0.15 parts calcium acetate, 0.1 parts antibacterial agent, total powder weight 100.19 parts; 0.92 parts liquid polycarboxylate superplasticizer (0.92% of total dry powder weight); 12.1 parts mixing water (12.08% of dry powder weight); total wet mix weight 113.21 parts; 6.56 parts alkali-resistant continuous glass fiber coarse sand (5.8% of wet mix weight).
[0039] Performance and effects: Density after adding fibers The initial flowability was 290 mm. After adding fibers and vibrating for 25 cycles on a jump table, the flowability was 180 mm. The 28-day shrinkage rate was... The compressive strength after 28 days is 120 MPa, and the flexural strength after 28 days is 17 MPa, meeting the mechanical properties of the decorative UHPC standard. The dosage of antibacterial agent is within the limits specified in this invention, and the 24-hour antibacterial rate against Escherichia coli and Staphylococcus aureus reaches 99.9%, while the antiviral activity rate against H1N1 influenza A virus reaches 99.9%, demonstrating excellent antibacterial and antiviral effects. It also possesses good construction fluidity and molding quality, making it suitable for manufacturing complex 3D curved decorative panels and reducing mold costs. Example 3:
[0040] Raw material proportions (parts by weight): 40.08 parts PW52.5 cement, 7.77 parts silica fume, 2.61 parts metakaolin, 1.57 parts expanding agent, 46.43 parts quartz powder, 1.48 parts adhesive powder, 0.15 parts calcium acetate, 0.1 parts antibacterial agent, total powder weight 100.19 parts; 0.92 parts liquid polycarboxylate superplasticizer (0.92% of total dry powder weight); 12.1 parts mixing water (12.08% of dry powder weight); total wet mix weight 113.21 parts; 4.53 parts alkali-resistant continuous glass fiber coarse sand (4.0% of wet mix weight).
[0041] Performance and effects: Density after adding fibers The initial flowability was 290 mm, and after adding fibers and vibrating for 25 cycles on a jump table, the flowability decreased to 220 mm, demonstrating superior flowability compared to other embodiments; the 28-day shrinkage rate was... It has a 28-day compressive strength of 95 MPa and a 28-day flexural strength of 14.5 MPa. Although its mechanical strength is slightly lower than other embodiments due to the fiber content being less than 5.8%, it still meets the decorative UHPC standard (compressive strength > 100 MPa, flexural strength > 12 MPa). It has excellent antibacterial and antiviral properties, with a 24-hour antibacterial rate of 99.9% against Escherichia coli and Staphylococcus aureus, and an antiviral activity rate of 99.9% against H1N1 influenza A virus. It is suitable for 3D curved surface decoration scenarios with moderate mechanical strength requirements and high flow performance requirements. Example 4:
[0042] Raw material proportions (parts by weight): 40.08 parts PW52.5 cement, 7.77 parts silica fume, 2.61 parts metakaolin, 1.57 parts expansion agent, 46.43 parts quartz powder, 1.48 parts adhesive powder, 0.15 parts calcium acetate, 0.1 parts antibacterial agent, total powder weight 100.19 parts; 1 part liquid polycarboxylate superplasticizer (0.998% of total dry powder weight); 12.1 parts mixing water (12.08% of dry powder weight); total wet mix weight 113.29 parts; 6.56 parts alkali-resistant continuous glass fiber coarse sand (5.8% of wet mix weight).
[0043] Performance and effects: Density after adding fibers The initial flowability was 300 mm, indicating good flow performance. After adding fibers and vibrating for 25 cycles on a jump table, the flowability decreased to 190 mm. The 28-day shrinkage rate was [missing information]. It exhibits excellent volume stability; its 28-day compressive strength is 135 MPa, and its 28-day flexural strength is 18.2 MPa, making its mechanical properties the best among all embodiments; its antibacterial and antiviral properties reach 99.9%, which can meet the manufacturing requirements of large, high-strength 3D curved UHPC decorative panels, significantly reducing the difficulty and cost of mold making, while ensuring human health. Example 5:
[0044] Raw material proportions (parts by weight): 40.08 parts PW52.5 cement, 7.77 parts silica fume, 2.61 parts metakaolin, 1.57 parts expansion agent, 46.43 parts quartz powder, 1.48 parts adhesive powder, 0.3 parts calcium acetate (chemically pure grade, dosage 0.3%), 0.1 parts antibacterial agent, total powder weight 100.34 parts; 0.92 parts liquid polycarboxylate superplasticizer (0.917% of total dry powder weight); 12.1 parts mixing water (12.06% of dry powder weight); total wet mix weight 113.36 parts; 6.56 parts alkali-resistant continuous glass fiber coarse sand (5.8% of wet mix weight).
[0045] Performance and effects: Density after adding fibers It has an initial flowability of 310mm, excellent flow properties, and is easy to apply by spraying; its 28-day shrinkage rate is [missing information]. It has a 28-day compressive strength of 120MPa and a 28-day flexural strength of 17MPa, with stable mechanical properties. The calcium acetate content reaches the upper limit, further optimizing the material's workability and early strength. The antibacterial and antiviral rates are both 99.9%, making it suitable for complex 3D curved decorative panel projects with high requirements for construction efficiency and early strength. Example 6:
[0046] Raw material proportions (parts by weight): 40.08 parts PW52.5 cement, 7.77 parts silica fume, 2.61 parts metakaolin, 1.57 parts expanding agent, 46.43 parts quartz powder, 2.5 parts adhesive powder, 0.15 parts calcium acetate, 0.1 parts antibacterial agent, total powder weight 101.21 parts; 0.92 parts liquid polycarboxylate superplasticizer (0.909% of total dry powder weight); 12.1 parts mixing water (11.96% of dry powder weight); total wet mix weight 114.23 parts; 6.56 parts alkali-resistant continuous glass fiber coarse sand (5.8% of wet mix weight).
[0047] Performance and effects: Density after adding fibers It is the lightest among all embodiments, facilitating transportation and installation; its initial flowability is 320 mm, and after adding fibers and vibrating for 25 cycles on a jump table, the flowability is 210 mm, exhibiting optimal flow performance and minimizing pipe blockage during spray molding; its 28-day shrinkage rate is [missing information]. It exhibits optimal volume stability; its 28-day compressive strength is 90MPa, and its 28-day flexural strength is 15.5MPa, meeting the decorative UHPC standard; it has an antibacterial and antiviral rate of 99.9%, making it suitable for 3D curved surface decoration scenarios with high requirements for self-weight, flow performance, and volume stability. The mold cost is low and the construction is convenient.
[0048] In summary, the following conclusions can be drawn regarding the verification of the technical effects: 1. Antibacterial and antiviral properties: In Example 1, the amount of antibacterial agent was only 0.05 parts, and the antibacterial rate and antiviral activity rate were 75% and 72.5%, respectively; while in Examples 2-6, the amount of antibacterial agent was 0.1 parts (within the range of 0.5-1.0 parts), and the antibacterial rate and antiviral activity rate both reached 99.9%. This proves that when the amount of antibacterial agent is within the range defined by this invention, the material can achieve a highly efficient and long-lasting antibacterial and antiviral effect, meeting the health requirements of decorative materials.
[0049] 2. Mechanical properties: In Example 3, the fiber content was 4.0% of the wet mix mass, and the 28-day compressive strength was 95 MPa and the flexural strength was 14.5 MPa. In Examples 1, 2, and 4-6, the fiber content was 5.8%, and the 28-day compressive strength was ≥120 MPa (Example 4 reached 135 MPa), and the flexural strength was ≥17 MPa (Example 4 reached 18.2 MPa). This shows that when the fiber content is controlled at 5.8%, the reinforcement and toughening effect is optimal, and the material fully meets the decorative UHPC standard (compressive strength > 100 MPa, flexural strength > 12 MPa).
[0050] 3. Volume stability: The shrinkage rate of each embodiment is within... The results showed that the synergistic effect of the expansion agent and metakaolin effectively controlled the shrinkage deformation of concrete, prevented the decorative panels from cracking during use, and improved durability.
[0051] 4. Construction performance: The initial flowability of each embodiment is 290-320mm, and the vibration flowability after adding fibers is 180-220mm, indicating that the material has good spray flowability and can smoothly form uniform surface and structural layers. It is especially suitable for the manufacture of complex 3D curved decorative panels. Compared with the traditional casting method, it greatly reduces the mold cost and manufacturing difficulty.
[0052] 5. Formulation compatibility: In Example 5, the calcium acetate content was 0.3 parts (upper limit), the initial flowability reached 310 mm, and the mechanical properties were stable; in Example 6, the adhesive powder content was 2.5 parts, and the bulk density decreased to The fluidity was improved to 320mm, proving that the formulation of this application can adjust the component dosage according to actual needs to adapt to different construction scenarios and performance requirements.
[0053] Therefore, the present invention, through precise control of the raw material ratio (especially key components such as antibacterial agents, fibers and water-reducing agents) and optimization of the spraying process, prepares antibacterial and antiviral sprayed ultra-high performance decorative concrete, which not only solves the pain points of traditional casting methods in the production of 3D curved decorative panels, but also has excellent mechanical properties and antibacterial and antiviral functions, adapting to the needs of different decoration scenarios and has strong practicality.
[0054] It should be noted that, in this invention, although the specification describes the embodiments, not every embodiment contains only one independent technical solution. This way of describing the specification is only for clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. An antibacterial and antiviral sprayed ultra-high performance decorative concrete, characterized in that, Includes dry powder, liquid polycarboxylate superplasticizer, and alkali-resistant continuous glass fiber coarse sand; The dry powder, by weight, comprises 40-45 parts white silicate cement, 5-10 parts silica fume, 2-5 parts metakaolin, 1-2 parts expansion agent, 40-50 parts natural colored sand, 1-1.5 parts redispersible latex powder, and 0.5-1.0 parts inorganic zinc oxide antibacterial agent. The amount of the liquid polycarboxylate superplasticizer used is 0.9-1.0% of the total mass of the dry powder. The amount of alkali-resistant continuous glass fiber coarse sand used is 5.8% of the wet mixture mass; The wet mix is made by mixing dry powder with mixing water, and the amount of mixing water is 11-13% of the mass of the dry powder; the compressive strength of the decorative concrete is >120MPa and the flexural strength is >12MPa.
2. The antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 1, characterized in that, The white silicate cement is PW52.5 grade, with a whiteness ≥85% and a specific surface area of [missing information]. .
3. The antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 1, characterized in that, The silica fume is a white zirconium-containing microsilica powder with a specific surface area of [missing information]. Zirconium oxide content ≥10%.
4. The antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 1, characterized in that, The average particle size of the inorganic zinc oxide antibacterial agent is ≤2μm.
5. The antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 1, characterized in that, The liquid polycarboxylate superplasticizer has a solid content of 50±1%, a pH value of 6.5±1, and a viscosity of <2000mPa·s.
6. The antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 1, characterized in that, The monofilament tensile strength of the alkali-resistant continuous glass fiber coarse sand elastic modulus The diameter of a single filament is ≤14μm.
7. A method for preparing antibacterial and antiviral sprayed ultra-high performance decorative concrete, characterized in that, Includes the following steps: (1) Stirring: According to the proportions described in claim 1, after the dry powder components are dry-mixed evenly, the pre-mixed liquid polycarboxylate superplasticizer and stirring water are added and wet-mixed to form a uniform wet mixture. (2) Preparation before spraying: Use a small CNC GRC spraying machine to adjust the fiber spraying speed so that the amount of alkali-resistant continuous glass fiber coarse sand meets the requirements of claim 1; (3) Surface spraying: Spraying wet mix containing alkali-resistant continuous glass fiber coarse sand into the mold to form a surface layer with a thickness of 1-5mm; (4) Structural layer spraying and compaction: Spray a wet mixture containing alkali-resistant continuous glass fiber coarse sand onto the surface layer to the specified thickness, and compact it by rolling it back and forth with a manual roller; (5) Surface smoothing: After removing excess material, smooth the surface to obtain antibacterial and antiviral sprayed ultra-high performance decorative concrete.
8. The method for preparing antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 7, characterized in that, In step (1), the dry mixing time is 5 min and the wet mixing time is 10 min.
9. The method for preparing antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 7, characterized in that, In step (2), before spraying, wet mixed material and alkali-resistant continuous glass fiber coarse sand are sprayed for 30 seconds each and weighed. The fiber spraying speed is adjusted according to the weighing results.
10. The method for preparing antibacterial and antiviral sprayed ultra-high performance decorative concrete according to claim 7, characterized in that, The liquid polycarboxylate superplasticizer is premixed with water and then added to the dry powder for wet mixing.